ENHANCING EDUCATION IN PROPERTY MANAGEMENT: THE DEVELOPMENT OF A SPECIALIZATION PROGRAM AT CIPUTRA UNIVERSITY SURABAYA - Ellen Lawrencia Yahya; Budidharmanto, Lexi Pranata; Dwi Sunu Widyo Pebruanto; Ni Putu Aryani; Devina Martina (Universitas Nahdlatul Ulama Surabaya, 2023)
In Indonesia, there is a high demand for skilled professionals in Property Management due to the increasing number of infrastructure projects. To bridge the gap between this demand and the availability of competent human resources, Ciputra University is undertaking a review of its academic curriculum to include a specialization program in Property Management. This study employed the Focus Group Discussion method to gain insights into people's perceptions and understanding of Property Management. The participants in the discussions consisted of faculty members and students from disciplines such as Hospitality and Tourism Business, as well as Interior and Architecture. This collaborative approach aimed to gather diverse perspectives necessary for developing the framework of the Property Management program.